Child Custody and the Principle of Best Interests in Divorce Decisions at the Makassar Religious Court: An Analysis of Maqashid al Syariah - Harid, Muh Asrhil; Ashufa, Abdul Hayyaqdhan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The high divorce rate in Indonesia has serious implications for child protection, particularly with regard to custody rights, which are often disputed in religious courts. In this context, the principle of the best interests of the child is a universal principle that judges must consider when determining custody rights. This study aims to examine the implementation of this principle in religious court practice through a case study of Decision Number 1278/Pdt.G/2023/PA.Mks at the Makassar Religious Court, while also reviewing its relevance to maqāṣid al-syarī‘ah. The research uses a qualitative approach with a theological-normative design, combining the analysis of positive legal documents, Islamic legal theory, and the maqāṣid al-syarī‘ah framework. Data was obtained through the study of decisions, Islamic family law literature, and supporting interviews, then analyzed through a process of reduction, categorization, and normative interpretation. The results of the study show that the panel of judges in this case not only considered formal legal aspects, but also psychological, emotional, social, economic, and child care environment factors as the basis for determining custody rights. These considerations reflect the application of the principle of the best interests of the child, as they place the welfare of the child above the interests of the parents. From the perspective of maqāṣid al-sharī‘ah, this decision is in line with the main objectives of sharia, namely the protection of life (ḥifẓ al-nafs), reason (ḥifẓ al-‘aql), and offspring (ḥifẓ al-nasl), so that it can be seen as a judicial practice that is responsive to Islamic values and contemporary social needs. Thus, this study emphasizes the importance of integrating the principle of the best interests of the child with maqāṣid al-syarī‘ah in religious court practices, while also contributing conceptually to the development of Islamic family law that is more adaptive, humanistic, and oriented towards child protection in Indonesia.